Strategic Groups in Banking - Amel, Dean F.; Rhoades, Stephen A. (The Review of Economics and Statistics, 1988)
The strategic groups hypothesis is tested using cluster analysis in -16 selected banking markets and based on portfolio composition in 1978, 1981, and 1984. The results indicate that approximately six strategic groups exist in banking and are stable over time. Strategy choices are similar across markets. Implications of the results are (1) intraindustry profit differences may be due to strategic groups rather than efficiency differences, (2) markets may generally be defined too broadly, (3) investigations for collusion need to focus on homogeneous groups in an industry rather than the whole industry, and (4) there is no simple strategy choice for banks between retail and wholesale banking.